2015
DOI: 10.1177/1747493015609777
|View full text |Cite
|
Sign up to set email alerts
|

Risk of early recurrent stroke in symptomatic carotid stenosis after best medical therapy and before endarterectomy

Abstract: Urgent aggressive BMT after index-event is associated with a significant reduction in the risk of early NR in CEA candidates. The early risk of recurrent stroke in patients with symptomatic significant carotid stenosis is dramatically reduced after urgent aggressive BMT in specialised stroke clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
(32 reference statements)
0
45
0
3
Order By: Relevance
“…But optimisation of secondary preventive pharmacotherapy during the waiting time between presenting event and carotid intervention may still substantially reduce the risk of a recurrent ischaemic event, both before and after the carotid procedure. 17,18,33 However, even if most stroke units routinely initiate best medical treatment, data are not available on this and thus it cannot be excluded that such a change over time partly explains the overall reduced risk.…”
Section: Discussionmentioning
confidence: 99%
“…But optimisation of secondary preventive pharmacotherapy during the waiting time between presenting event and carotid intervention may still substantially reduce the risk of a recurrent ischaemic event, both before and after the carotid procedure. 17,18,33 However, even if most stroke units routinely initiate best medical treatment, data are not available on this and thus it cannot be excluded that such a change over time partly explains the overall reduced risk.…”
Section: Discussionmentioning
confidence: 99%
“…Shahdi et al 11) reported that urgent aggressive, best medical therapy may reduce the risk of early recurrent stroke in patients awaiting CEA. They suggested that its higher procedural risks may argue against urgent revascularization surgery soon after symptom onset and recommended delaying surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemická CMP je jednou z hlavních příčin úmrtnosti a disability [1]. Navíc platí, že roční riziko rekurentní CMP činí přibližně 37 % a že riziko rekurence iCMP během 14 dnů dosahuje hodnoty 20 % [2,3]. Podle randomizovaných klinických studií představuje karotická endarterektomie (carotid endarterectomy, CEA) účinnou chirurgickou metodu prevence CMP tehdy, jestliže četnost pooperačních komplikací u pacientů se symptomatickou stenózou vnitřní karotické tepny (ICA) je nižší než 6 % [4].…”
Section: úVodunclassified
“…Vzhledem k vyššímu riziku intracerebrálního krvácení po iCMP bylo a je doporučováno odložit CEA na dobu čtyř až šest týdnů po CMP [5]. Nová data ovšem dokládají, že CEA provedená do 14 dnů po CMP není spojena s vyšším rizikem rekurence CMP než CEA realizovaná za čtyři až šest týdnů po CMP [3,6]. V posledních letech se často objevovaly také zprávy o vhodnosti a účinnosti CEA u symptomatických pacientů provedené do tří dnů, či dokonce během prvních šesti až osmi hodin od prvních příznaků CMP [2,6].…”
Section: úVodunclassified
See 1 more Smart Citation